O princípio de composicionalidade em Frege como possibilidade de tratamento das atitudes proposicionais - Castelucci, Marcella Dehara Pereira (2019)
Propositional attitudes are a subject involved in many philosophy of language problems discussed on the writings of Frege, such as the distinction on sense and reference. Propositional attitudes consist of a mental phenomena in which the object is identified as a proposition, and this is what makes it possible for it to be semantically analyzed. Such analysis investigate the truth value of the propositions performed on many mental states. By examining the composition of the necessary elements to the comprehension of the meaning of a name or a sentence, Frege acknowledged a new objective semantic element, the thought. The Fregean explanational scheme covers different semantic possibilities, since it proposes that a name or an expression points to the sense and not to the object that it denotes, by means of a indirect reference. Such feature of his semantic theory will support the verification of sentences involving propositional attitudes, associated with the application of his compositionality principle and respecting the Leibniz's s substitutability principle.